Brain herniation on computed tomography is a poor predictor of whether patients with a devastating brain injury can be confirmed dead using neurological criteria. (November 2022) - Ray, Andrew; Manara, Alex R; Mortimer, Alex M; Thomas, Ian
Background: It is unclear if the presence of compartmental brain herniation on neuroimaging should be a prerequisite to the clinical confirmation of death using neurological criteria. The World Brain Death Project has posed this as a research question. Methods: The final computed tomography of the head scans before death of 164 consecutive patients confirmed dead using neurological criteria and 41 patients with devastating brain injury who died following withdrawal of life sustaining treatment were assessed by a neuroradiologist to compare the incidence of herniation and other features of cerebral swelling. Results: There was no difference in the incidence of herniation in patients confirmed dead using neurological criteria and those with devastating brain injury (79% vs 76%, OR 1.23 95%, CI 0.56–2.67). The sensitivity and specificity of brain herniation in patients confirmed dead using neurological criteria was 79% and 24%, respectively. The positive and negative predictive value was 81% and 23%, respectively. The most sensitive computed tomography of the head findings for death using neurological criteria were diffuse sulcal effacement (93%) and basal cistern effacement (91%) and the most specific finding was loss of grey-white differentiation (80%). The only features with a significantly different incidence between the death using neurological criteria group and the devastating brain injury group were loss of grey-white differentiation (46 vs 20%, OR 3.56, 95% CI 1.55–8.17) and presence of contralateral ventricular dilatation (24 vs 44%, OR 0.41, 95% CI 0.20–0.84). Conclusions: Neuroimaging is essential in establishing the cause of death using neurological criteria. However, the presence of brain herniation or other signs of cerebral swelling are poor predictors of whether a patient will satisfy the clinical criteria for death using neurological criteria or not. The decision to test must remain a clinical one.